Motif Pelanggaran Netralitas Aparatur Sipil Negara dalam Pemilihan Kepala Daerah Kabupaten Solok Tahun 2020 - Wahib Assyahri; Dio Prasetyo Budi; Mercya Vaguita; Rahmi Suci; Nia Rahmadhani (Journal of Education on Social Science (JESS), 2022)
As the executor of government policies, the State Civil Apparatus (ASN) upholds the principles that have been established based on the laws and regulations, one of which is the principle of neutrality. However, violations of ASN neutrality cannot be avoided, this problem is influenced by various motives. The Regional Head Election (pilkada) in Solok district in 2020. To see these motives, the authors conducted research using descriptive qualitative methods. Informants from the research were determined by purposive sampling technique. Data were taken by interview, observation, and documentation. Then the data is processed by source triangulation. So that the research results show that violations of ASN neutrality occur due to internal motives and external motives. The internal motives are the desire to get a better position and the emotional closeness between ASN and the candidate pair. Internally, the position is threatened if it does not side with one of the candidates who are predicted to win. The limited authority of Bawaslu in terms of following up on ASN who commits a violation is a gap for ASN to commit a violation